FORMULASI DAN UJI AKTIVITAS ANTI JAMUR OBAT KUMUR EKSTRAK SARANG SEMUT (Myrmecodia platyrae) TERHADAP JAMUR Candida Albicans - Rusmin, Rusmin (Jurnal Kesehatan Yamasi Makassar, 2023)
Abstract. This study aims to make a mouthwash formula from ant nest extract (Myrmecodia platyrae) using various extract concentrations of 5%w/v, 10% w/v and 15% w/v. The research design used was laboratory experimental. In this study, ant nest extract was formulated into a mouthwash with a concentration of F1 5% w/v, F2 10% w/v and F3 15% w/v and then activity was tested against Candida albicans using the paper disk method. Physical stability tests for mouthwash preparations using ant nest extract included organoleptic tests, pH tests, homogeneity tests, and stability tests as well as phytochemical screening tests. Based on the results of the study obtained from ant nest extract mouthwash inhibition zone which was produced during the incubation period of 1 x 24 hours F1 10.40 mm, F2 11.32 mm, F3 11.88 mm, positive control 14.67 and during the incubation period 2 x 24 hours obtained F1 11.34 mm, F2 12.02 mm, F3 12.91, positive control 26.44 indicating an inhibitory effect on the growth of Candida albicans